The Land of Israel (Eretz Yisra’el) in Jewish and Christian Understanding - Lux, Richard C. (Studies in Christian-Jewish Relations, 2011)
One of the principal issues confronting Christians in the dialogue is the significance of the land in the Jewish and Christian Scriptures. This article explores the significance of the Land of Israel in the Scriptures as land given, retained and holy – especially to Christians. The history of the significant Christian religious relationship to the land is reviewed and finally a re-imaging of our relationship to the Holy Land in terms of a post-Vatican II expansion of our understanding of Catholic sacramental theology is suggested: that as Christ is the sacrament of encounter with God, so the Holy Land is a sacrament of our encounter with Christ.